Community Empowerment in Preventing Non-Communicable Diseases Through the Utilization of Family Medicinal Plants (Toga) - Sri Mulyati; Rasyid (Poltekkes Kemenkes Semarang, 2026)
Non-communicable diseases (NCDs) such as hypertension and diabetes mellitus remain major public health problems worldwide [1,2]. This community service program aimed to improve community knowledge and awareness in preventing NCDs through the utilization of Family Medicinal Plants (TOGA). The activity was conducted in Meteseh Subdistrict, Semarang City, involving PKK women. Methods included pre-test assessment, free health screening, interactive education, physical exercise, and post-test evaluation. The program demonstrated increased community understanding of NCD prevention and TOGA utilization. Integrated education and empowerment activities effectively support sustainable community health promotion. Non-communicable diseases (NCDs) such as hypertension and diabetes mellitus remain the leading causes of morbidity, mortality, and health financing burden in Indonesia. The increasing prevalence of NCDs poses a significant challenge to the sustainability of the national health system, including the National Health Insurance (JKN). Comprehensive and preventive approaches based on community empowerment are therefore urgently needed in line with the pillars of Indonesia’s Health System Transformation. This community service program aimed to strengthen community capacity in preventing NCDs through integrated health education, early screening, and the utilization of Family Medicinal Plants (Tanaman Obat Keluarga/TOGA) as culturally appropriate preventive resources, while supporting digital health integration through the SATU SEHAT platform. The program was conducted in Meteseh Subdistrict, Semarang City, involving members of the PKK women’s group. Methods included pre-test assessment, blood pressure and random blood glucose screening, interactive education on NCD prevention and TOGA utilization, healthy heart exercise sessions, and post-test evaluation. The results demonstrated improved community knowledge regarding NCD risk factors, preventive behaviors, and evidence-based utilization of TOGA such as ginger, turmeric, lemongrass, and galangal. The program also increased awareness of routine health monitoring and data integration within the national health information system. This study concludes that community empowerment integrating traditional resources, lifestyle modification, and digital health awareness effectively supports NCD prevention and contributes to health system resilience. Sustained community engagement and policy alignment are essential to ensure long-term impact.